2018
DOI: 10.1155/2018/3753547
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent Human Mesenchymal Stem Cells Are More Resistant to Heat Stress than Cycling Cells

Abstract: Quiescence is the prevailing state of many cell types under homeostatic conditions. Yet, surprisingly, little is known about how quiescent cells respond to environmental challenges. The aim of the present study is to compare stress responses of cycling and quiescent mesenchymal stem cells (MSC). Human endometrial mesenchymal cells (eMSС) were employed as adult stem cells. eMSC quiescence was modeled by serum starvation. Sublethal heat shock (HS) was used as a stress factor. Both quiescent and cycling cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…In contrast to the apoptotic reaction of 3D eMSC, heat shock induced a stop in the proliferation of damaged monolayer cells (Figure 6A), which was accompanied by a prolonged S-G 2 /M cell cycle block (Figure 6C) and expression of active senescence-associated β-galactosidase (Figure 6D). These results confirmed our previously published data and gave evidence about the induction of the SIPS program in 2D eMSC cultures that survived sublethal thermal stress (Alekseenko et al, 2014(Alekseenko et al, , 2018. To check whether 3D eMSCs that survived heat shock undergo stress-induced senescence, heated spheroids were dissociated 3 h after the stress, plated, and then were further cultured under adhesive monolayer conditions.…”
Section: D Emscs Respond To Stress By Activating the Stress-induced Premature Senescence Programsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to the apoptotic reaction of 3D eMSC, heat shock induced a stop in the proliferation of damaged monolayer cells (Figure 6A), which was accompanied by a prolonged S-G 2 /M cell cycle block (Figure 6C) and expression of active senescence-associated β-galactosidase (Figure 6D). These results confirmed our previously published data and gave evidence about the induction of the SIPS program in 2D eMSC cultures that survived sublethal thermal stress (Alekseenko et al, 2014(Alekseenko et al, , 2018. To check whether 3D eMSCs that survived heat shock undergo stress-induced senescence, heated spheroids were dissociated 3 h after the stress, plated, and then were further cultured under adhesive monolayer conditions.…”
Section: D Emscs Respond To Stress By Activating the Stress-induced Premature Senescence Programsupporting
confidence: 90%
“…Our analysis of the 3D eMSC cell cycle (Domnina et al, 2018) showed that cells in spheroids do not proliferate that means they are less susceptible to the DNA-damaging stress factors. In contrast to eMSCs from spheroids, actively proliferating monolayer cells are more sensitive to the genotoxic effect of stress (Alekseenko et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…In hematopoietic stem cells of mice, non-homologous end-joining mediated repair but not HR repair is preferentially used for repair of DNA damage during the quiescence phase (Mohrin et al, 2010). The detection frequency of γH2AX foci induced by heat stress in quiescent human endometrial mesenchymal cells (MSCs) is considerably lower than that in proliferating MSCs (Alekseenko et al, 2018). Thus, it is suggested that the mechanism of DNA repair in QC cells also differs substantially from that in differentiated cells and stem cells in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge of molecular and cellular biology of cellular senescence S. Kobashigawa et al The sensitivity of heat stress depends on the cell cycle phase. Cycling cells are found to be more sensitive to heat stress than quiescent cells 85) . In addition, cellular response to heat stress in early S phase is different than in other phases 79) .…”
Section: - -mentioning
confidence: 98%